Pengaruh Harga dan Lokasi Terhadap Keputusan Pembelian Konsumen Pada Produk Minuman Teh Nora di Sicincin - Nini; Nurofik, Agus (Jurnal Pustaka Manajemen (Pusat Akses Kajian Manajemen), 2025)
With the increasing trend of contemporary drinks in various age groups, especially young people, it shows the great business opportunities in this business. However, several factors such as price and location variables must be considered for the sustainability of the business in this field. This study aims to determine the effect of price and location on consumer purchasing decisions on Teh Nora beverage products located in Sicincin, West Sumatra Province. In this study, the researcher chose a quantitative method. The population used was Teh Nora consumers with a sample of 40 people determined based on the purposive sampling technique. The data used came from primary data collected through questionnaires. And for data analysis, this study used multiple linear regression tests using SPSS version 30.0. The results of the study showed that price (X1) with a sig. <0.001 partially (alone) had a significant effect on purchasing decisions (Y), as well as location (X2) with a sig. <0.001 also partially (alone) had a significant effect on purchasing decisions (Y). While simultaneously both price (X1) and location (X2) also had a significant effect on purchasing decisions (Y) with a sig. <0.001.